2017
DOI: 10.1007/s12070-017-1217-z
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Laryngoscopy in Management of Congenital Stridor

Abstract: The incidence of congenital stridor is on rise due to improved neonate and infant survival rate. The gold standard investigation for evaluation of stridor is rigid laryngotracheobronchoscopy, but this is invasive and requires general anesthesia. Flexible fibreoptic laryngoscopy, a relatively simple and less invasive procedure can be done under topical anaesthesia for evaluation of stridor. In this study, we have presented our experience of flexible laryngoscopy in children with congenital stridor, their result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…[25].In our study, the most common etiology of chronic stridor was found to be subglottic stenosis followed by laryngomalacia. In most previous studies, laryngomalacia has been the most common cause of chronic stridor in children [26][27][28]. However, a survey conducted by Cadd et al in 2005 also described the rising incidence of subglottic stenosis and multiple laryngeal pathologies in children with stridor [29] In our study, we could find only one case out of thirty-five patients of chronic stridor where stridor was due to vocal cord paralysis.…”
Section: Discussioncontrasting
confidence: 47%
“…[25].In our study, the most common etiology of chronic stridor was found to be subglottic stenosis followed by laryngomalacia. In most previous studies, laryngomalacia has been the most common cause of chronic stridor in children [26][27][28]. However, a survey conducted by Cadd et al in 2005 also described the rising incidence of subglottic stenosis and multiple laryngeal pathologies in children with stridor [29] In our study, we could find only one case out of thirty-five patients of chronic stridor where stridor was due to vocal cord paralysis.…”
Section: Discussioncontrasting
confidence: 47%
“…The role of FFL in the workup of SDB has been limited to incongruence between symptoms and degree of ATH as well to evaluate other symptoms not consistent with obstructive sleep apnoea from ATH, including stridor. There is a dearth of literature on the utility of FFL and the number needed to treat to identify other sources of obstruction in the routine workup of patients with these conditions 4…”
Section: Introductionmentioning
confidence: 99%
“…(2) There are various methods available for diagnosis of such cases-radiological, rigid laryngotracheobronchoscopy and fibreoptic laryngoscopy. (3) The approach to such a case and its subsequent management varies from case to case. (4) Treatment strategy for each possible cause varies.…”
mentioning
confidence: 99%